Hypophosphatasia and its role in bone pathology in adults - K. E. Zotkina; O. M. Lesnyak (Лечащий Врач)
Pathogenesis and symptoms of hypophosphatasia were reviewed, in particular in adults, as well as methods of diagnostics and treatment.